Under surveillance: an actor network theory ethnography of users’ experiences of electronic monitoring - Berry, Carl R. (European journal of criminology, 2021)
Electronic monitoring (EM) tags are a punishment that utilizes surveillance to enforce curfews. This capacity has drawn debate as to whether it simply enforces the penalty or exists as a punishment itself. However, little empirical work has been conducted on users regarding the experience. The encroaching presence of mass surveillance has also been increasingly debated within criminology, amidst concerns concerning the capabilities of technologies to monitor and control citizens. This article will explore the impact of surveillance as a specific feature of EM to investigate how being monitored is experienced by users during sentences. It will principally draw upon the ethnographic approach of actor network theory – which argues that humans and non-human technologies ‘relationally’ coexist with each other – to explore this phenomenon.